Delignification of Cassava Peel as Bioethanol Raw Material using Combined Alkali and Microwave Heating Methods. Issue 1 (1st June 2022) - Hartulistiyoso, Edy; Farobie, Obie; Zaky, M
Abstract: Indonesia is ranked fourth as the largest cassava producing country with a total production of around 20 million tons per year. As much as 15-20% per kilogram of cassava is waste in the form of cassava peel which contains starch and allows it to be converted into alternative energy such as bioethanol. The bioethanol production process is carried out through the stages of pretreatment (delignification) to obtain cellulose used in the hydrolysis process, hydrolysis, fermentation, and purification. This paper discussed the use of combined alkali and microwave heating methods to increase the cellulose content and reduce the lignin content of cassava peel. Delignification was carried out by varying the NaOH concentration of 0.5, 0.75, and 1 M and microwave exposure of 5, 10, and 15 min. The data of the pretreatment variation were statistically tested using a completely randomized design. The results shows that combined alkali and microwave heating methods was able to increase cellulose content from 39.78 to 59.01 %, decrease hemicellulose content from 24.75 to 12.79 %, and decrease lignin content from 23.28 to 14.66 %. The combination of 1 M NaOH and 15 min microwave exposure showed the best results.